The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.joc.1c01303
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Regulated Palladium-Catalyzed Regiodivergent Hydroarylation of the Distal Double Bond of Allenamides with Aryl Boronic Acid

Abstract: The ligand-regulated regiodivergent hydroarylation of the distal double bond of allenamides with aryl boronic acid was achieved in the presence of palladium­(II) catalysts, delivering a variety of functionalized enamide with excellent E selectivity and Markovnikov/anti-Markovnikov selectivity. Two possible coordination intermediates were proposed to be responsible for the regiodivergent hydroarylation: (1) The coordination Intermediate I, which was proposed to be formed through the coordination of MeCN, distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…While the formation of C−C bonds was not a primary objective of our study, it is worth noting that only one example is reported in the literature describing the γ-addition of anisole to allenamides. 31 This protocol is limited to allenyl-N-sulfonamides and its sustainability is penalized by the use of boronic acids, a Pd-based catalyst, and 1,4-dioxane as the solvent. In all other protocols, anisole was unreactive, since many more electron-rich compounds must be used to ensure an acceptable reactivity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the formation of C−C bonds was not a primary objective of our study, it is worth noting that only one example is reported in the literature describing the γ-addition of anisole to allenamides. 31 This protocol is limited to allenyl-N-sulfonamides and its sustainability is penalized by the use of boronic acids, a Pd-based catalyst, and 1,4-dioxane as the solvent. In all other protocols, anisole was unreactive, since many more electron-rich compounds must be used to ensure an acceptable reactivity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, HFIP is characterized by a certain acidity (p K a ∼ 17.9 in DMSO, p K a ∼ 9.3 in water). While the formation of C–C bonds was not a primary objective of our study, it is worth noting that only one example is reported in the literature describing the γ-addition of anisole to allenamides . This protocol is limited to allenyl- N -sulfonamides and its sustainability is penalized by the use of boronic acids, a Pd-based catalyst, and 1,4-dioxane as the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Liu and coworkers disclosed a palladium‐catalyzed hydroarylation of monosubstituted N‐ tosyl allenamides (Scheme 49). [52] The use of acetonitrile as a ligand mainly led to the addition of the aryl moiety onto the terminal carbon of the allene (Scheme 49, eq. 1) whereas the use of the bulkier dppf or Xantphos ligand instead afforded the product resulting from the addition on the central carbon of the allene (Scheme 49, eq.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of our recently developed cyclization of allenamides, [52][53][54][55][56][57][58][59][60] we envisioned a plausible Csp 3 -H bond activation of the allylic position, which might undergo hydrogen atom transfer to deliver pyrroline derivates as shown in Scheme 1D. However, the chemo-and regio-selectivity and low BDE distinction between the old and new CÀ H bond are the main challenging.…”
Section: Introductionmentioning
confidence: 99%